The Importance of Cell Geometry and Electrolyte Properties to the Cell Potential of Zn-Ce Hybrid Flow Batteries. Issue 1 (1st January 2016) - Arenas, L. F.; Walsh, F. C.; de León, C. Ponce
Abstract : This paper considers the effects of electrolyte resistivity and inter-electrode gap on the simulated cell potential of an idealized Zn-Ce unit flow cell as a function of applied current density. The thermodynamic, kinetic and ohmic components of cell potential in a redox flow battery (RFB) are taken into account. This is important in the Zn-Ce RFB, where the positive electrode reaction tends to govern cell performance. The ionic conductivity of methanesulfonic acid (MSA) and typical electrolytes reported in the literature was measured as a function of MSA concentration and temperature. At 50°C, the ionic resistivity of the positive and negative electrolytes is 3.0 Ω cm and 4.8 Ω cm respectively, for the most favorable electrolyte composition. The simulated cell potential showed that high surface-area electrodes were beneficial to the cell performance, while electrolytes containing 0.8 mol dm −3 Ce(III) and 1.5 mol dm −3 Zn(II) produced the lowest ohmic drop, which decreased at higher temperatures. The activation overpotential and internal resistance can be the main potential loss component, depending on electrolyte composition, cell design and electrode materials. The effect of cell geometry on the cell potential was also assessed, larger inter-electrode gaps significantly increasing potential losses.